2022
DOI: 10.3390/life12091441
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Analysis Reveals Sex-Specific Alternative Splicing Events in Zebrafish Gonads

Abstract: Alternative splicing is an important way of regulating gene functions in eukaryotes. Several key genes involved in sex determination and gonadal differentiation, such as nr5a1 and ddx4, have sex-biased transcripts between males and females, suggesting a potential regulatory role of alternative splicing in gonads. Currently, the sex-specific alternative splicing events and genes have not been comprehensively studied at the genome-wide level in zebrafish. In this study, through global splicing analysis on three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
1
1
Order By: Relevance
“…Indeed, regarding Experiment 1, cancer does not appear to be associated with differential sex-specific mortality at the embryonic stage, nor does it play a role in sex determination (since both phenomena would have skewed the sex-ratio). These results contrasts with numerous studies that have identified sex-specific responses in zebrafish regarding various factors (e.g., (Zhou et al 2010, Li et al 2019, Giommi et al 2022, Lin et al 2022, Park et al 2022, van Gelderen et al 2022, Zhai et al 2022, Zheng et al 2022, Zhong et al 2023)), including cancers (e.g., (Lee et al 2018, 2021, Mensah et al 2019, Montal et al 2023)). One possible explanation is that the cancer type used in our study may have too low aggressiveness, as possibly evidenced by the ability of individuals affected at the embryo stage to develop into adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, regarding Experiment 1, cancer does not appear to be associated with differential sex-specific mortality at the embryonic stage, nor does it play a role in sex determination (since both phenomena would have skewed the sex-ratio). These results contrasts with numerous studies that have identified sex-specific responses in zebrafish regarding various factors (e.g., (Zhou et al 2010, Li et al 2019, Giommi et al 2022, Lin et al 2022, Park et al 2022, van Gelderen et al 2022, Zhai et al 2022, Zheng et al 2022, Zhong et al 2023)), including cancers (e.g., (Lee et al 2018, 2021, Mensah et al 2019, Montal et al 2023)). One possible explanation is that the cancer type used in our study may have too low aggressiveness, as possibly evidenced by the ability of individuals affected at the embryo stage to develop into adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…AS has been widely studied in model organisms like Drosophila melanogaster , Danio renio or Caenorhabditis elegans (Zahler, 2005, Venables, Tazi and Juge, 2012, Lin et al, 2022). In Drosophila melanogaster AS plays important roles in sex-determination, muscle, neural development among other biological processes (Venables, Tazi and Juge, 2012).…”
Section: Introductionmentioning
confidence: 99%